Experiências e vivências em territórios de luta uma interconexão com a educação popular - Soares, Rosalinda Falcão (2023)
This thesis entitled “Experiences and Living in Territories of Struggle: an interconnection with popular education” presented to the Popular Education Research Line of the Postgraduate Program in Education (PPGE) of the Federal University of Paraíba (UFPB) addresses some established movements in the area of knowledge of public education. This is qualitative research. The general objective of the research proposes to analyze three experiences in the field of education knowledge, in delimitation, the Popular Education Campaign (CEPLAR) in the 1950s-1960s, Paulo Freire's Management project at the Municipal Education Secretariat in São Paulo- capital (1989-1992) in the interconnection with the experience of Countryside Education in Rural Settlements in the municipality of Sapé, state of Paraíba. This is a qualitative-based research and the theoretical-methodological path used the foundations of Popular Education, in the interface with Freirean Pedagogy, among other exponents who dialogue with this theoretical framework, which made it possible to get closer to different researchers, such as Arroyo; Caldart; Molina (2009); Beisiegel(1992); Brandão(1984;2002;2016;2019); Carrilho (2013); Quiet(2011); Favero (1992); Freire(1991; 1979; 1992; 1996; 1999; 2003; 2005); Méjía (2018); Le Goff (2013); Silva (2003); Stedile (2002). In the woven plot it is possible to identify the interconnection between the experiences of popular education in the city of Sapé with the other experiences being delimited in the research, considering the particularities of each of them. The evidence indicates that these experiences are interconnected, especially in the political, economic, social and cultural dimensions, driven by democratic processes in their respective historical times.